1997
DOI: 10.1007/s002239900353
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro and In Vivo Study of Cytokines in the Acute-Phase Response Associated with Bisphosphonates

Abstract: We studied the acute phase response, including specific cytokine production, [interleukin-1 (IL-1), interleukin-6 (IL-6), tumor necrosis factor alpha(TNF alpha)] following a single dose of Aredia (disodium pamidronate) in patients with increased bone turnover and, in vitro, the role played by specific cytokines in the acute-phase reaction which may follow the administration of aminobisphosphonates. An in vivo exploratory study was done on 24 in- and outpatients with increased bone turnover given a single intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
1
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 11 publications
10
113
1
7
Order By: Relevance
“…Nitrogen-containing bisphosphonates (such as alendronate) induce various inflammatory reactions via interleukin dependent mechanisms. [27][28][29][30] Bisphosphonate-induced inflammation exacerbates pathologic conditions such as arthritis 31 and atherosclerosis. 32 Blockage of matrix metalloproteinases improves anterior cruciate graft healing in the bone tunnels.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen-containing bisphosphonates (such as alendronate) induce various inflammatory reactions via interleukin dependent mechanisms. [27][28][29][30] Bisphosphonate-induced inflammation exacerbates pathologic conditions such as arthritis 31 and atherosclerosis. 32 Blockage of matrix metalloproteinases improves anterior cruciate graft healing in the bone tunnels.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3) The fever was noted to be associated with a fall in circulating lymphocyte number (1,4) and increases in circulating IL-6 (4) and tumor necrosis factor-alpha (TNF-a) (4)(5)(6) but not interleukin (IL)-1. (6) This is referred as the acute phase response (APR). N-BPs inhibit osteoclastic bone resorption by blocking farnesyl-pyrophosphate-synthase, an enzyme in the mevalonate pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown the positive effect of systemic bisphosphonate treatment in protecting the peri-implant bone, either around cemented [15] or around uncemented implants [42]. However, side effects like fever [29,40], throat, or stomach ulcers [9] as well as a low bioavailability [16] are generally observed for systemic bisphosphonate treatment. In order to avoid these adverse effects and to increase the bisphosphonate bioavailability, the systemic treatment following a total hip replacement (THR) could be replaced by a local delivery with the implant selectively coated with bisphosphonate.…”
Section: Introductionmentioning
confidence: 99%